GeNeDis 2014 : Geriatrics - Vlamos, Panayiotis; Alexiou, Athanasios (Advances in Experimental Medicine and Biology,, 2015)
The 1st World Congress on Geriatrics and Neurodegenerative Disease Research (GeNeDis 2014), will focus on recent advances in geriatrics and neurodegeneration, ranging from basic science to clinical and pharmaceutical developments and will provide an international forum for the latest scientific discoveries, medical practices and care initiatives. Advances information technologies will be discussed along with their implications for various research, implementation and policy concerns. In addition, the conference will address European and global issues in the funding of long-term care and medico-social policies regarding elderly people. GeNeDis 2014 takes place in Corfu, Greece, 10-13 April 2014. This volume focuses on the sessions that address geriatrics.